Awareness, perception and practice of stakeholders in India regarding Village Health and Nutrition Day - Panigrahi, Sandeep K. (J Family Med Prim Care, 2015)
BACKGROUND: Village Health and Nutrition Day (VHND) is a community-based health service package delivered on a fixed day approach. Services like early registration of pregnancy, regular antenatal care and postnatal care, growth monitoring and referral of sick children, discussion of health topics to generate awareness, and convergence between health and ICDS, are delivered every month at VHND at the Anganwadi Center. This study explores the awareness, perception and practice of service providers, and beneficiaries, regarding VHND. MATERIALS AND METHODS: It was a cross-sectional study conducted in Odisha during December 2009–November 2010. Personal interviews were conducted at the VHND sessions with 111 beneficiaries and 45 service providers using a semi-structured schedule to know their awareness, perception and practice regarding VHND sessions. Data analysis was done and reported as simple percentages. RESULTS: Most of the health worker females and anganwadi workers considered health awareness as a key component of VHND. 52% of HWFs and 41% of AWWs had misconception about additional roles and responsibilities. 34% of beneficiaries had knowledge regarding fixed day approach of VHND, while 24% did not have knowledge regarding any of its purpose. Only 8% of referral cases had complete knowledge on the reason of referral. There was significant difference in between awareness and practice among the blocks. CONCLUSION: Service providers’ orientation should be improved. Behavior change communication activities should also be increased by the state. Referral cases should be properly counseled. The community believed that such a program should continue with better package and quality of services.